STRATEGI PENINGKATAN PRAKTIK PEMBERIAN ASI EKSKLUSIF - Yekti Widodo; Heryudarini Harahap; Sri Muljati; Agus Triwinarto (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2003)
STRATEGY TO IMPROVEMENT EXCLUSIVE BREASTFEEDING COVERAGEBackground: Exclusive breastfeeding practice in Indonesia not yet gratified, ranging from 3,6% up to 27,5%. Therefore require to be developed a promotion strategy to motivate the exclusive breastfeeding, by entangling target of besides mother with given by a complete information about exclusive breastfeeding. Objectlves: Knowing exclusive breastfeeding promotion impact to coverage of exclusive breastfeeding. Methods: This research represent the research observational, with kohort design. Sampel research is all pregnancy women which old age its pregnancy have entered the third trimester. All sampel research given the counselling with interpersonal communication and non-formal condition and also the discussion with husband, parent, grandmother. At this research the strategy counselling to motivate the exclusive breastfeeding by giving information about exclusive breastfeeding, creating condition and environment supporting, improving husband involvement, other family member, traditional birth attendant, cadre, and rural midwife (bidan di desa) and also lessen the negative consequence, like busy, baby rewel, and insufficient breastfeeding. Counselling conducted by special worker which have been trained, since the pregnant women in third trimester until the baby 4 month ages. Results: Total sampel in this research is 221 all family have been given the motivation for the pracllcaly of exclusive breastfeeding. From 221 sampel gave the motivation 110 sampel (49,8%) earning given exclusive breastfeeding during 4 month, while 111 sampel (50,2%) cannot given exclusive breastfeeding because some reason among other things: husband, arent, and or parent in law not support, feel too busy, child need the practice eat, fear later child become difficult eat. This applying counselling strategy can motivate the mother to give the exclusive breastfeeding during 4 month reach 49,8%. This matter indicate that this strategy is good enough to increase exclusive breastfeeding coverage. Conclusions: Counselling strategy with infonnal communications and while non-formal condition and given the complete information and also to combining discussion with the counselling target, is good enough to motivate and look after the exclusive breastfeeding gift behavior. Recommendations: Applying of strategy counselling in order to exclusive breastfeeding promotion need the commitment all of health worker to support and also have to entangle the husband, parent, parent in law, and traditional birth attendant as counselling target. Keywords: exclusive breastfeeding, counselling exclusive, breastfeeding improvement